A wandering small bowel stromal tumor with a challenging imaging diagnosis - Masino, Federica; Tupputi, Ruggiero; Montatore, Manuela; D'Arma, Giuseppe Maria Andrea; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2024)
We report a rare case of a small bowel stromal tumor, occurring in a 57-year-old female patient and presenting as an abdominal wandering mass on imaging. The woman came to the emergency room complaining of recurrent diffuse abdominal pain, weight loss, and presenting anemia. She underwent an urgent CT scan of the abdomen that revealed the presence of a lower abdominal right mass of not easily recognizable origin. Subsequently, the patient was hospitalized, and an MRI was requested. The examination showed the same mass with a different location, having moved on the upper left side of the abdomen. An ultrasound was also performed to get a complete overview of imaging features. The mobile abdominal mass made imaging diagnosis challenging, which led to the hypothesis of a GIST, confirmed by histopathological biopsy.